2014
DOI: 10.1105/tpc.114.130781
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Dependent Repression of theArabidopsisFloral Integrator Genes Involves Plant Specific PHD-Containing Proteins  

Abstract: The interplay among histone modifications modulates the expression of master regulatory genes in development. Chromatin effector proteins bind histone modifications and translate the epigenetic status into gene expression patterns that control development. Here, we show that two Arabidopsis thaliana paralogs encoding plant-specific proteins with a plant homeodomain (PHD) motif, SHORT LIFE (SHL) and EARLY BOLTING IN SHORT DAYS (EBS), function in the chromatin-mediated repression of floral initiation and play in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 62 publications
(100 reference statements)
5
102
2
3
Order By: Relevance
“…The abundance of H3K4me3 and H3K9ac histone modifications changes at specific loci during numerous developmental transitions in plants (Kim et al, 2008(Kim et al, , 2009a(Kim et al, , 2012Charron et al, 2009;Adrian et al, 2010;Anzola et al, 2010;van Dijk et al, 2010;Brusslan et al, 2012;Malapeira et al, 2012;López-González et al, 2014;Molitor et al, 2014;Schenke et al, 2014), and thus, it is likely that the final stage of leaf development, leaf senescence, would be accompanied by changes in these two well-characterized histone modifications that positively correlate with gene expression. Leaves were harvested from progressively more senescent plants and subject to RNA-seq and ChIP-seq, so that a direct correlation between gene expression and Table II.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of H3K4me3 and H3K9ac histone modifications changes at specific loci during numerous developmental transitions in plants (Kim et al, 2008(Kim et al, , 2009a(Kim et al, , 2012Charron et al, 2009;Adrian et al, 2010;Anzola et al, 2010;van Dijk et al, 2010;Brusslan et al, 2012;Malapeira et al, 2012;López-González et al, 2014;Molitor et al, 2014;Schenke et al, 2014), and thus, it is likely that the final stage of leaf development, leaf senescence, would be accompanied by changes in these two well-characterized histone modifications that positively correlate with gene expression. Leaves were harvested from progressively more senescent plants and subject to RNA-seq and ChIP-seq, so that a direct correlation between gene expression and Table II.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, RPD3, the ortholog of Arabidopsis HDA6, has been shown to be part of a large protein complex that includes transcriptional repressors such as Switch Independent3 and Unscheduled Meiotic gene Expression1 (Grzenda et al, 2009). And there is evidence that plant HDAs also operate in multiprotein complexes containing histone-binding proteins, corepressors, and associated proteins (Gu et al, 2011;Perrella et al, 2013;López-González et al, 2014). It is thus possible that the hda6-8 mutation in the E-R motif affects the interaction of HDA6 with the complex.…”
Section: A Highly Conserved Domain In Hda6 Is Required For Its Targetmentioning
confidence: 99%
“…S6). We selected histone marks that are usually located within genes and that were previously analyzed for florigen genes of other plant species (Jiang et al, 2008;Adrian et al, 2010;He, 2012;Sun et al, 2012;Gu et al, 2013;Mascheretti et al, 2013;López-González et al, 2014). Four histone marks usually associated with active transcription were selected for chromatin analysis.…”
Section: Variation Of Zcn7 and Zcn8 Transcript Isoform Levels Under Fmentioning
confidence: 99%
“…FT, a phosphatidylethanolamine-binding protein, then moves from leaves through the phloem to the shoot apical meristem (Corbesier et al, 2007;Jaeger and Wigge, 2007), where it interacts with a basic Leu zipper domain transcription factor encoded by FLOWERING LOCUS D (FD) to induce the expression of floral identity genes, such as APETALA1 (Abe et al, 2005;Wigge et al, 2005). Recently, it was shown that chromatin-related mechanisms play an important role in regulating FT expression (He, 2012;Gu et al, 2013;Bu et al, 2014;López-González et al, 2014;Wang et al, 2014).…”
mentioning
confidence: 99%